2019
DOI: 10.3390/math7111120
|View full text |Cite
|
Sign up to set email alerts
|

Sine-Cosine Algorithm to Enhance Simulated Annealing for Unrelated Parallel Machine Scheduling with Setup Times

Abstract: This paper presents a hybrid method of Simulated Annealing (SA) algorithm and Sine Cosine Algorithm (SCA) to solve unrelated parallel machine scheduling problems (UPMSPs) with sequence-dependent and machine-dependent setup times. The proposed method, called SASCA, aims to improve the SA algorithm using the SCA as a local search method. The SCA provides a good tool for the SA to avoid getting stuck in a focal point and improving the convergence to an efficient solution. SASCA algorithm is used to solve UPMSPs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…In this experiment, we compare the results of δ of MHHO with other methods using small-size problems as in Table 3. These methods including the traditional HHO, and SSA, SA [75], T9 [74], T8 [74]. From these results, it can be observed that the MHHO outperforms other methods, especially the SA, T9, and T8.…”
Section: Results Of δ Over Small-size Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment, we compare the results of δ of MHHO with other methods using small-size problems as in Table 3. These methods including the traditional HHO, and SSA, SA [75], T9 [74], T8 [74]. From these results, it can be observed that the MHHO outperforms other methods, especially the SA, T9, and T8.…”
Section: Results Of δ Over Small-size Problemsmentioning
confidence: 99%
“…Equation 1is the fitness function of UPMS problems that requires minimizing the value of C max . More details can be found in [74,75].…”
Section: Problem Definitionmentioning
confidence: 99%
“…Moreover, the ABC algorithm was effectively applied on several MTS tasks, it suffers from some drawbacks, such as taking more time to explore the population, requiring many numbers of iterations to reach the optimal solution, and can get stuck in local minima, therefore, in this paper the ABC is improved using the Sine-Cosine Algorithm (SCA) to minimize these drawbacks. The SCA algorithm has many advantages such as low computation requirement and few predefined parameters that provide stable results; it had been applied to solve several problems, for instance [19]- [24].…”
Section: Introductionmentioning
confidence: 99%
“…The SCA is employed to optimize the parameters of the ANFIS. In Reference [ 31 ], the authors applied SCA to enhance simulated annealing (SA) algorithm to build an efficient model for scheduling jobs in unrelated parallel machines that can be employed in manufacturing scheduling applications. In Reference [ 32 ], the SCA is applied to enhance the artificial bee colony (ABC) that applied for image segmentation.…”
Section: Introductionmentioning
confidence: 99%